Analisis Kinerja Keuangan Sebelum dan Sesudah Initial Public Offering (IPO) Pada Perusahaan Non Keuangan di Bursa Efek Indonesia - Arfandi Arfandi; Salma Taqwa (Universitas Negeri Padang, 2018)
Deciding for an initial public offering (IPO) has a major influence in improving the company's condition, improving the company's performance, especially in terms of corporate financial performance. This study aims to assess financial performance by viewing and analyzing financial reports, non-financial companies that IPO in 2014 at BEI. Financial analysis uses 6 (six) financial ratios: Return On Investments (ROI), Net Profit Margin (NPM), Total Asset Turn Over (TATO), Current Ratio, Debt to Equity Ratio (DER), and CashFlow Operation Ratio (CashFlow to Sales). Assessment of financial performance by comparing the difference in performance before IPO with post IPO so that the data analysis technique used is paired sample T-test. Based on the results of the analysis found that there are differences in financial performance in the current ratio, and the ratio of total asset turnover (TATO) before and after the IPO, but there is no difference in financial performance measured through return on investment (ROI), net profit magin (NPM ), debt to equity ratio (DER), and cash flow operations ratio. The condition of performance difference in current ratio tends to increase seen from the average value before doing IPO but TATO ratio tends to decrease from before IPO.Keyword: Initial Public Offering (IPO), Financial Performance, Financial Ratio